Can symptoms help in differential diagnosis between substance-induced vs independent psychosis in adults with a lifetime diagnosis of cocaine use disorder? - Vergara-Moragues, Esperanza; Mestre-Pintó, Joan I; Araos, Pedro; Rodríguez-Fonseca, Fernando; González-Saiz, Francisco (Psychiatry Research, 2017)
The main goal of this study it is explore the psychopathological differences between IPD and SIPD in a sample of 125 adults with a lifetime diagnosis of cocaine disorder recruited from treatment setting and through street contacts. A secondary analysis of six cross-sectional studies was conducted between 2000 and 2010. SIPD and IPD were diagnosed using the Psychiatric Research Interview for Substance and Mental Disorders (PRISM). 38 subjects (30.4%) were diagnosed with lifetime IPD and 87 (69.6%) with lifetime SIPD. A binomial logistic regression analysis using SIPD as the reference group showed that only previous prison admissions (OR 2.59; 95% CI 1.05, 6.36) and visual hallucinations (OR 5.21; 95% CI 1.54, 17.65) remained significant variables in the group with lifetime SIPD. In the group with lifetime IPD, grandiose delusions (OR 0.19; 95% CI 0.06, 0.60) and disorganized speech (OR 0.16; 95% CI 0.04, 0.61) remained significant. Model predicts the diagnosis of lifetime SIPD with a sensitivity of 80.3% and a specificity of 78.2%. This clinical profile of lifetime SIPD could help distinguish between IPD and SIPD among adults with lifetime diagnosis of cocaine disorder.
Keywords: psychosis; substance use; substance-induced; schizophrenia; cocaine; JCR; Scopus